(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This article is based on the analysis of the results of anthropological, archaeological, ethnohistorical, and physical anthropology research carried out in Nicaragua on roles of woman in the past, who left their stories in clay figurines, monexicos made from stone, tombs of warriors and in the the historical ethnography written by the chroniclers of the indies based only on observations of their daily life of our autochthonous societies. These results show that women were not only beautiful, maternal and responsible for activities in their homes but they were also leaders, councilors, chiefs, warriors, caciques, sukias, among other roles that have survived in their collective memory to manifest itself in current societies in which women have been recovering their lost rights and moving towards a more fair Nicaragua on a sociocultural level.